2020
DOI: 10.1016/j.ijpharm.2020.119782
|View full text |Cite
|
Sign up to set email alerts
|

A novel treatment strategy for preterm birth: Intra-vaginal progesterone-loaded fibrous patches

Abstract: Progesterone-loaded poly(lactic) acid fibrous polymeric patches were created for the intra-vaginal application using electrospinning (ES) and pressurized gyration (PG) to prevent preterm birth with higher bioavailability. The patches were intravaginally inserted into the rats in the final week of their pregnancy, equivalent to the third trimester of human pregnancy. Maintenance tocolysis with progesterone-loaded patches was elucidated by recording the contractile response of uterine smooth muscle to noradrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…The main parameters that affect the formation and homogeneity of nanofibrous scaffolds are ambient conditions such as temperature and humidity, process conditions such as working pressure and rotational speed for PG; working distance, polymer solution feed rate, applied voltage for electrospinning, solution properties such as viscosity, density, surface tension, and in addition for electrospinning, electrical conductivity. [47,48] These parameters were recorded for each solution (Table S1a).…”
Section: Physical Properties Of Solutionsmentioning
confidence: 99%
“…The main parameters that affect the formation and homogeneity of nanofibrous scaffolds are ambient conditions such as temperature and humidity, process conditions such as working pressure and rotational speed for PG; working distance, polymer solution feed rate, applied voltage for electrospinning, solution properties such as viscosity, density, surface tension, and in addition for electrospinning, electrical conductivity. [47,48] These parameters were recorded for each solution (Table S1a).…”
Section: Physical Properties Of Solutionsmentioning
confidence: 99%
“…The fact that PLA gave a few peaks that were not sharp has indicated that PLA is far from the crystalline structure. [ 39,40 ]…”
Section: Resultsmentioning
confidence: 99%
“…More recently, progesterone loaded PLA scaffolds were fabricated for intra-vaginal therapy using both ES and pressurised gyration; with the latter engineering patches with superior tensile strength and production yield compared to ES. However, the ES process found to yield much thinner fibers (between average of 6.06 µm and 7.893 µm) [399].…”
Section: Pressurised Gyrationmentioning
confidence: 95%